A local solution to the Navier–Stokes equations on manifolds via stochastic representation. (September 2020) - Ledesma, Diego S.
Abstract: We obtain a C k local existence result for the Navier–Stokes equations on compact Riemannian manifolds using the representation formula for the solution obtained by Fang and Luo.